A Positive Framework to Analyze Sovereign Bail-outs within the EMU - Christian Fahrholz; Cezary Wójcik (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2011)
We propose a positive formal framework for analyzing sovereign bail-outs in the context of the European Monetary Union (EMU) with a view to making policy recommendations regarding improvements to the EMU institutional architecture. We build our analysis on a political economic game-theoretic model that allows tracing analytically the dynamics of the political process as well as the conditions and parameters on which the scope and limits of the bail-outs depend. In doing so, we formally take account of the negative externality' problem that has been central to policy debates related to the EMU's institutional design and has played an important role in the recent crisis. Contrary to the existing literature, we do not only focus on the economic aspects of such a negative externality, but also look at where they emanate from and interact with the dynamics of the political formation within the EMU. The analysis suggests that, under the present political-economic set-up of the EMU, the bail-outs were inevitable, i.e. a threat of default by one member must, under identifiable conditions, result in sharing the costs of fiscal adjustment by the rest of the members.
urn:nbn:de:gbv:27-20131118-110554-0
Keywords: E62; F33; H77; C70; 330; Sovereign debt crisis; bail-out; negative externality; political economics; game theory; euro; EMU; Schuldenübernahme; Staatsbankrott; Neue politische Ökonomie; Spieltheorie; Externer Effekt; Eurozone; Theorie